An evolutionary approach to optimising synthetic apomixis in cereal crops - Šurbanovski, Nada (2022)
Seed-mediated apomixis evolved as an alternative to the reproductive pathway whereby unreduced cells within the ovule acquire a reproductive fate. A recent breakthrough study showed that male-derived expression of the transcription factor BBM1 in rice, which triggers the embryonic programme upon fertilisation, can be used to deliver parthenogenesis when ectopically expressed in the oocyte. Feasibility of apomixis in rice was shown by combining the BBM1 expression in the egg with a mitosis/meiosis substitution construction known as MiMe.